Author Correction: Cryo-EM structure of a fungal mitochondrial calcium uniporter. (25th October 2018) - Nguyen, Nam; Armache, Jean-Paul; Lee, Changkeun; Yang, Yi; Zeng, Weizhong; Mootha, Vamsi; Cheng, Yifan; Bai, Xiao-chen; Jiang, Youxing
In this Article, ref. 15 has been replaced and references 32 to 50 have been renumbered online.